Nepalese initiatives in poverty research: moving from uni-to-multidimensional concepts and measurements - Adhikari, Keshab Prasad (Nepal Population Journal, 2018)
The aged long conventional unidimensional definition and measurement of poverty ‘lack of money’ in most countries is being replaced by the multidimensional approach and methodology. The launching of MPI report in 2018 implied Nepal also officially to adopt this in national poverty measurement policy strategy. This paper is aimed at to sensitize methodological aspects of MPI among academic and policy implications in Nepalese context. Debate on multidimensional poverty research in addressing rampant poverty dates back the advent of basic-needs and the physical quality of life index approaches of 1970s but both failed to establish a valid and reliable deprivation score to divide population as poor and non-poor like in income line approach. Human development index gave basis to rank countries into four groups as very high, high, medium and low level of human development. However it could not offer a precise deprivation score to divide population into-two as in absolute deprivation and non-deprivation as well as population in borderline of deprivation as alternatives of income poverty. It is the Alkire and Foster’s (2007 and 2010) MPI methodology/approach of OPHI and successively adopted in human development reports of UNDP, aggressively being adopted as alternatives of conventional income line methods of poverty measurement and targeting policies. Three dimensional and ten indicators equally weighted MPI based on the same conceptual groundings of ‘capability, wellbeing and functions’ of Sen are taken as reliable alternative to the conventional income approach of poverty measurement. With the official release of national MPI study report in January 2018, Nepal adopted MPI in its policy option in targeting population living in multiple web of poverty and their targeting. The study found poverty and deprivation studied from MPI perspective is vital to attain multiple goals of 2030 SDGs.